Teaching English to Gen Z English Learners: What are their responses to General English Topics? - Nahdi, Khirjan; Setiawan, Budi; Wathoni, Hamzani; Basri, Hasan (IJE : Interdisciplinary Journal of Education, 2024)
Studies on General English topics that are pertinent to Generation Z are scarce, particularly in Indonesia. This study, thus, intends to examine the framework of questions on what the relevant general English topics are for Generation Z English learners. The census was implemented with quantitative-descriptive as an approach for this investigation. Additionally, this study used an online questionnaire shared using Google Forms to 680 first-year students out of 1560 targeted participants to collect data. The final statistics of this study were displayed by dividing the total number of responses into percentages using Microsoft Excel 2010. The findings of this analysis revealed that the topics of Introduction and Daily Activity were the most popular topics. Giving directions is also the least interesting subject, followed by describing places, procedural text, and reviews of popular tourist destinations. These topics are disliked for a variety of reasons, such as confusion, trouble understanding the language, limited vocabulary, beginner-level skills. Furthermore, the majority of the participants thought the topics of Introduction, Daily Activity, and Procedural Text (What to Need) were quite relevant. The reviews of tourist destinations and Living abroad, on the other hand, scored lower for relevancy. The results imply that Generation Z English learners favor subjects that are simple to study, have practical uses, and use basic, everyday language. Based upon the investigation, exploring potential strategies or approaches that could make these topics more engaging and relevant to Generation Z learners could also be explored in future research.